2020
DOI: 10.1038/s41598-020-75284-2
|View full text |Cite
|
Sign up to set email alerts
|

Colour matters more than shape for chimpanzees’ recognition of developmental face changes

Abstract: Social primates must recognise developmental stages of other conspecifics in order to behave appropriately. Infant faces have peculiar morphological characteristics—relatively large eyes, a small nose, and small mouth—known as baby schema. In addition, the infant faces of many primate species have unique skin coloration. However, it is unclear which features serve as critical cues for chimpanzees to recognise developmental changes in their faces. The present study aimed to investigate the relative contribution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 58 publications
1
37
0
Order By: Relevance
“…Eight adult and eight infant faces (four female and four male faces for each), which were used in a previous study [19], were delineated by 118 landmarks as described previously [19]. The original images depicted faces of chimpanzee infants aged 2-10 months and adults aged 13-22 years at the time the pictures were taken.…”
Section: Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…Eight adult and eight infant faces (four female and four male faces for each), which were used in a previous study [19], were delineated by 118 landmarks as described previously [19]. The original images depicted faces of chimpanzee infants aged 2-10 months and adults aged 13-22 years at the time the pictures were taken.…”
Section: Stimulimentioning
confidence: 99%
“…By contrast, of approximately half of all primate species [24], infants have unique skin and/or coat coloration that differs from that of adults [24][25][26][27]. Indeed, statistical image quantification has demonstrated that chimpanzee infants also have both unique facial shape and colour characteristics [19]. Chimpanzee infant faces have some baby-schematic characteristics such as bigger eyes located lower in faces and curved supraorbital torus, which contrasts with the straight ones in adults.…”
Section: Introductionmentioning
confidence: 99%
“…to PP). With a wealth of material at its disposal, archaeology can draw on a rich seam of visual psychological research, as over the last two decades, visual psychologists have devoted considerable attention to the study of facial information processing, from the specialization of areas of the brain for processing faces and using facial information to discriminate social status in inferotemporal cortex or emotional states in the amygdala (Pessoa and Adolphs 2010;Tsao et al 2003;Said, Haxby, and Todorov 2011;Little, Jones, and DeBruine 2011), to the more comparative undertakings of facial processing by adults, children and chimpanzees (Schofield et al 2019;Kawaguchi, Nakamura, and Tomonaga 2020). One only has to look at our propensity for seeing faces in natural objects such as clouds, slices of toast or electric plug sockets to understand just how central to human evolution the rapid processing of facial information was.…”
Section: Faces and Facingmentioning
confidence: 99%
“…For example, Koda et al (2013) examined whether Japanese macaques (Macaca fuscata) exhibit an attentional bias for infant faces, which has been reported in humans (Lucion et al 2017), but they obtained no evidence to support this. Other studies found that non-human primates can differentiate between faces of different age categories (i.e., adult or infant) (Kawaguchi et al 2019b(Kawaguchi et al , 2020. In these studies, chimpanzees (Pan troglodytes) (Kawaguchi et al 2020) and capuchin monkeys (Sapajus apella) (Kawaguchi et al 2019b) were trained to discriminate between the adult and infant faces of conspecifics or humans using a symbolic matching-to-sample task.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found that non-human primates can differentiate between faces of different age categories (i.e., adult or infant) (Kawaguchi et al 2019b(Kawaguchi et al , 2020. In these studies, chimpanzees (Pan troglodytes) (Kawaguchi et al 2020) and capuchin monkeys (Sapajus apella) (Kawaguchi et al 2019b) were trained to discriminate between the adult and infant faces of conspecifics or humans using a symbolic matching-to-sample task. Both the chimpanzees and capuchin monkeys easily learned to do this, and this ability was generalized to the discrimination of novel stimuli.…”
Section: Introductionmentioning
confidence: 99%